2021
DOI: 10.7554/elife.69438
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic preconditioning in astrocytes mitigates trauma-induced neurodegeneration

Abstract: Concussion is associated with a myriad of deleterious immediate and long-term consequences. Yet the molecular mechanisms and genetic targets promoting the selective vulnerability of different neural subtypes to dysfunction and degeneration remain unclear. Translating experimental models of blunt force trauma in C. elegans to concussion in mice, we identify a conserved neuroprotective mechanism in which reduction of mitochondrial electron flux through complex IV suppresses trauma-induced degeneration of the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…106 While the specific mechanism behind why DGLA and its metabolites, DHED, are more detrimental to dopaminergic neurons remains unknown, Fonseca et al reported a similar vulnerability of different neuron types in response to biomechanical injury and suggested that such observation could be due to different physiological regulatory mechanisms between different neuron types. 107 Such neuron-type-specific effects triggered by DGLA and DHED warrant future investigation to uncover potential new neurodegeneration mechanisms. However, investigating ferroptosis to understand differential ferroptosis mechanisms between tissues requires studies being carried out at the system level, which is challenging owing to the lack of appropriate genetic and imaging tools.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…106 While the specific mechanism behind why DGLA and its metabolites, DHED, are more detrimental to dopaminergic neurons remains unknown, Fonseca et al reported a similar vulnerability of different neuron types in response to biomechanical injury and suggested that such observation could be due to different physiological regulatory mechanisms between different neuron types. 107 Such neuron-type-specific effects triggered by DGLA and DHED warrant future investigation to uncover potential new neurodegeneration mechanisms. However, investigating ferroptosis to understand differential ferroptosis mechanisms between tissues requires studies being carried out at the system level, which is challenging owing to the lack of appropriate genetic and imaging tools.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Our results complement previous studies by Zille et al, which showed that different cell types could have distinct regulatory pathways for ferroptosis . While the specific mechanism behind why DGLA and its metabolites, DHED, are more detrimental to dopaminergic neurons remains unknown, Fonseca et al reported a similar vulnerability of different neuron types in response to biomechanical injury and suggested that such observation could be due to different physiological regulatory mechanisms between different neuron types . Such neuron-type-specific effects triggered by DGLA and DHED warrant future investigation to uncover potential new neurodegeneration mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…reported a similar vulnerability of different neuron-types in response to biomechanical injury and suggested that such observation could be due to different physiological regulatory mechanisms between different neuron types. 87 Such neuron type-specific effects triggered by DGLA and DHED warrant future investigation to uncover potential new neurodegeneration mechanisms. Investigating ferroptosis at the systems level to understand differential ferroptosis mechanisms between tissues is challenging, owing to the lack of appropriate genetic and imaging tools.…”
Section: Discussionmentioning
confidence: 99%
“…et al, which showed that different cell types could have distinct regulatory pathways for ferroptosis 86. While the specific mechanism behind why DGLA and its metabolites, DHED, are more detrimental to dopaminergic neurons remains unknown, Solano Fonseca et alreported a similar vulnerability of different neuron-types in response to biomechanical injury and suggested that such observation could be due to different physiological regulatory mechanisms between different neuron types 87. Such neuron type-specific effects triggered by DGLA and DHED warrant future investigation to uncover potential new neurodegeneration mechanisms.…”
mentioning
confidence: 99%
“…As a member of the major redox shuttle in neurons, the absence of ARALAR leads to an inability to metabolize lactate [ 25 , 26 ] and thus severely compromises the function of the astrocyte-to-neuron lactate shuttle, which has an important protective role under neurodegenerative and physiological conditions [ 65 , 66 , 67 ]. This aspect will be further discussed in Section 4.1 .…”
Section: Agc1/slc25a12/aralar-mas Pathway In Brain Metabolismmentioning
confidence: 99%